COMPARATIVE ANALYSIS OF STOCK PRICES OF PT. UNILEVER, TBK BEFORE AND AFTER THE ISRAELPALESTINE CONFLICT BOYCOTT CAMPAIGN - Ach. Royandi; Aprilya Dwi Yandari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2026)
The aim of this study is to find out whether the price of Unilever stocks had changed before and after the boycott announcement. The research methodology uses a quantitative approach with an event study; stock price data is collected over 60 days, 30 days before and 30 days after the announcement of the boycott. This research uses IBM SPSS version 25 to perform data analysis. The results of the analysis in this study, showed that the boycott campaign did not significantly affect the share price return of PT. Unilever, Tbk Indonesia. In addition, in terms of trading activity volume (VAT), the stock price before and after the boycott did not change significantly